E-Payment System Readiness of Micro Business Owners - Allan B. Pleno (Research Synergy Foundation, 2024)
This study used qualitative research to examine e-payment system readiness among microbusiness owners in Region III, Philippines. The primary purpose was to explore four key themes: digital literacy and skills, comparisons between cash and e-payment transactions, the downsides of e-payment, and awareness and capacity for e-payment systems. Data were collected through thematic coding of interviews with ten microbusiness owners. The results revealed that most respondents actively engage with digital technology, using mobile devices and computers daily. While internet access is generally available, reliance on mobile data can affect user experience. Findings indicate that cash transactions remain prevalent; however, there is a noticeable shift toward e-payments due to their convenience in bill payments and online shopping. Significant challenges were identified, including technical issues and unreliable internet connections that hinder smooth transactions. Older users and those with limited technological skills face difficulties in adopting such systems. The study concludes that although there is potential for greater adoption of e-payment systems, addressing infrastructure challenges and enhancing digital literacy—especially among older demographics—is crucial for facilitating a full transition. Targeted training initiatives and reliable technology are essential for improving e-payment readiness among microbusinesses in the region.